BELANJA PUBLIK (EXPENDITURE ASSIGNMENT) ANTARA MASALAH DAN EFEKTIVITAS ANGGARAN BELANJA - Neny Ayu Nourmanita (Yogyakarta State University, 2016)
This paper discusses the problems of public budgets, particularly in government spending. The discussion will be more emphasized on aspects of government and discussed about the issue of the effectiveness of public spending, especially in the case studies of Magetan district. This paper used qualitative descriptive method. The collection of data obtained through secondary data and analysis document. Data were analyzed with interactive model, through data reduction, data presentation, and conclusion.Discussion of the results shows that overall government spending and areas in Indonesia can not be said to be healthy and in accordance with the needs of the community. Their dominance of indirect expenditure in the form of personnel expenditure sector remains deeply embedded in the budget. Both on the expenditure and the shopping area, both have similarities in personnel expenditure dominance were very swollen. Besides government spending and shopping area cannot provide the impact poverty reduction and improvement of people's welfare.Keywords: Public Expenditure, Government Budgets, APBD, APBN.